Technology Innovation Support in Development of Local Superior Shallot in North Sulawesi - Olvie Grietjie Tandi; F. Faisal (Universitas Sembilanbelas November Kolaka, 2020)
The need for Shallot at the community level continues to increase every year in line with the increase in population. Shallots are used as cooking spices and used in the herbal medicine industry. Minahasa Regency is one of the centers of shallot development in North Sulawesi, where production at the farm level is still below the average of 7-8 t/ha. For this reason, a breakthrough in cultivation technology innovation is needed to increase yields. This writing aims to provide information on technological innovation support in the effort to develop local superior shallots in North Sulawesi and to see the results of farming from the application of the technology. The data obtained from the results of interviews and research results both conducted by the North Sulawesi AIAT Assessment Team and other research results. The support of technological innovation in efforts to develop shallots is the application of onion PTT Innovations: land management, preparation of plant spacing, use of certified seeds, planting and fertilizing, watering and controlling weeds, controlling plant pests, harvesting and post-harvesting. The conclusions obtained by the application of PTT shallots, which were examined by BPTP North Sulawesi using local varieties Lansuna. The B / C ratio is 4.23 by giving an income of Rp. 273,058,000 compared to the way of farmers where B / C ratio = 2.23 with income of Rp. 138,233,000 / hectare